Editing author main entry towards complying standards: study on original catalogue of Jaffna public library - Ketheeswaren, S. (Journal of the University Librarians Association of Sri Lanka, 2017)
The catalogues of the libraries should follow a common standard. While maintaining accepted cataloging standards by libraries, method of searching and retrievals for a book would be uniform, meaningful and responsive. Libraries need to make studies on their catalogue entries to ensure that they are providing such uniform, meaningful and responsive searching and retrievals from the library catalogue. In this scenario, the study is made on the purpose of understanding the deviations of standards that occurs in the original catalogue of Jaffna Public Library. The deviation is measured by using a sample of randomly selected titles of the original catalogue of the Jaffna Public Library for complying with cataloguing standards. The necessary comparison is made against the same title in the library of congress to identify the deviation types and measure the corresponding numbers of edits. The study identifies three major types and eight sub types of deviations (edits) that are required to be rectified to comply with cataloguing standards on author main entry (MARC Tag 100$a). Among the sub-types of edit, the editing of “correctly selecting author entries” (whether personal-name, corporate-name, meeting-name or uniform-title?) is found as predominant edit in the author main entries. Full-stop mistake is found as common mistake for all author main entries. Moreover, the paper extends through discussion on all major and sub types of deviations of cataloguing standards by putting the normalized values of editing percentage in tables and figures, while providing necessary recommendation to systematically rectify all types of deviations that are currently left in the catalogues and maintain accepted cataloging standards during future data entering.
Keywords: Cataloging; Library catalogs